Immunosuppression induced by co-exposure to allergens and PM2.5 increases the risk of lung disease upon viral protein challenge - Dong Im Kim; Mi-Kyung Song; Ji Eun Yuk; Jiyoung Park; Jiwon Choi; Kyuhong Lee (Environment International)
Particulate matter (PM2.5) and allergens are common environmental exposures. However, their combined effects and their risks are still poorly understood. This study aimed to investigate the impact of co-exposure to house dust mites (HDM) allergens and diesel exhaust particles (DEP) on lung immune responses, and assess the susceptibility to viral protein. We found that compared with HDM alone, mice co-exposed to HDM and DEP showed DEP-phagocytosed macrophages in lungs and did not show asthma phenotypes, including T helper 2 (Th2) response, eosinophilic inflammation, mucus production, and serum immunoglobulin E (IgE) production. Mechanistically, DEP induced an immunosuppressive state by suppressing HDM-induced Th2 responses by reducing FcγRIIB and FcγRIII-mediated phagocytosis and antigen presentation in the lungs. Notably, short-term exposure to the SARS-CoV-2 spike protein subunit 1 (S1) in altered immune environment led to the development of pulmonary fibrosis. This was accompanied by elevated transforming growth factor-β1 expression, increased total IgE levels, and eosinophil infiltration in the lungs. These findings suggest that co-exposure to PM2.5 and allergens causes a vulnerable lung environment that enhances susceptibility to virus-induced lung diseases. Our study emphasizes the need for more comprehensive environmental health assessments that account for the combined risks of PM2.5, allergens, and viral exposures.